اسلامی ادب کا دائرۂ کار اور امتیازات: Scope and Peculiarities of Islamic Literature (Al-Qamar, 2022)
Islamic literature has many distinctions in its contents, aims and objectives, which are certainly not found in any heavenly or non-heavenly religion. Therefore, there is a step-by-step invitation to the harmony of knowledge and practice, the relationship between morals and character, leaving bad habits, the beauty of words and meaning, comprehensiveness and universality, moderation and the formation of character. Its appearance is not separated from its inner being, there is no complexity, ambiguity and contradiction in its teachings. While the prose literature of Islam is distinguished with all these distinctions, all these essentials are kept in mind in its poetic literature as well.  Islamic literature has such an influence due to its beauty, distinction, clarity, simplicity, aims and objectives, that the heart and mind are drawn towards its effective words and effective meaning.  This influence is impressive to its listeners and readers in every form, from the beautiful recitation of the Qur’an and Hadith to the poetic collections.
Keywords: Literature; Islam; targets; Effects